2022
DOI: 10.1007/s12520-021-01499-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying biological affinities of Holocene northern Iberian populations through the inner structures of the upper first molars

Abstract: Neolithisation was a relatively fast process that affected both the interior and coastal zones of the Iberian Peninsula, but it was also a heterogeneous process that had diverse impacts on genomic and cultural diversity. In the Late Neolithic–Chalcolithic, a change in funerary practices, cultural material and trade networks occurred, and genomic heterogeneity decreased, suggesting human mobility and genetic admixture between different Iberian populations. Dental morphology has emerged as an effective tool for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…While the Cova de l'Avi group had a mixed diet with the substantial inclusion of extrinsic particles resulting from food processing, at Cova de Can Sadurní, highly refined pre‐processing of food can be inferred with distinctive characteristics that set it apart from other contemporaneous groups. This is relevant because dental morphology studies have suggested that the individuals from Cova de Can Sadurní could be a closed group with limited interactions to other groups (Gamarra et al, 2022; Pascual et al, 2018). This isolation may have led to distinct technological and cultural specializations in food processing for each group.…”
Section: Discussionmentioning
confidence: 99%
“…While the Cova de l'Avi group had a mixed diet with the substantial inclusion of extrinsic particles resulting from food processing, at Cova de Can Sadurní, highly refined pre‐processing of food can be inferred with distinctive characteristics that set it apart from other contemporaneous groups. This is relevant because dental morphology studies have suggested that the individuals from Cova de Can Sadurní could be a closed group with limited interactions to other groups (Gamarra et al, 2022; Pascual et al, 2018). This isolation may have led to distinct technological and cultural specializations in food processing for each group.…”
Section: Discussionmentioning
confidence: 99%